Assessment of Myocardial Work in Cancer Therapy-Related Cardiac Dysfunction and Analysis of CTRCD Prediction by Echocardiography - Guan, Jingyuan; Bao, Wuyun; Xu, Yao; Yang, Wei; Li, Mengmeng; Xu, Mingjun; Zhang, Yu; Zhang, Mei (Frontiers in Pharmacology, 2021)
No study has examined myocardial work in subjects with cancer therapy-related cardiac dysfunction (CTRCD). Myocardial work, as a new ultrasonic indicator, reflects the metabolism and oxygen consumption of the left ventricle. The aim of this study was to test the relative value of new indices of myocardial work and global longitudinal strain (GLS) in detecting changes in myocardial function during the treatment of breast cancer by two-dimensional and three-dimensional echocardiography. We enrolled 79 breast cancer patients undergoing different tumor treatment regimens. Follow-up observation was conducted before and after chemotherapy. The effects of breast cancer chemotherapy and targeted therapy on the development of CTRCD (defined as an absolute reduction in LVEF of >5% to <53%) were detected by two-dimensional and three-dimensional speckle tracking echocardiography. Our findings further indicate that left ventricular ejection fraction (LVEF), myocardial work index (GWI) and myocardial work efficiency (GWE) showed significant changes after the T6 cycle, and GLS showed significant changes after the T4 cycle (p<0.05). The three-dimensional strain changes after T6 and T8 had no advantages compared with GLS. Body mass index (BMI), the GLS change rate after the second cycle of chemotherapy (G2v) and the 3D-GCS change rate after the second cycle of chemotherapy (C2v) were independent factors that could predict the occurrence of CTRCD during follow-up, among which BMI was the best predictor (area under the curve, 0.922). In conclusion, the current study determined that GLS was superior to GWI in predicting cardiac function in patients with tumors with little variation in blood pressure. BMI, G2v and C2v can be used to predict the occurrence of CTRCD.